Political allegory in late medieval England - Astell, Ann W. (Ithaca : Cornell University Press, 1999)
Ann W. Astell here affords a radically new understanding of the rhetorical nature of allegorical poetry in the late Middle Ages. She shows that major English writers of that era-among them, William Langland, John Gower, Geoffrey Chaucer, and the Gawain-poet-offered in their works of fiction timely commentary on current events and public issues. Poems previously regarded as only vaguely political in their subject matter are seen by Astell to be highly detailed and specific in their veiled historical references, implied audiences, and admonitions.Astell begins by describing the Augustinian and Boethian rhetorical principles involved in the invention of allegory. She then compares literary and historical treatments of key events in fourteenth- and fifteenth-century England, finding an astonishing match of allusions and code words, especially those deriving from puns, titles, heraldic devices, and personal cognizances, as well as repeated proverbs, prophecies, and exempla. Among the works she discusses are John Ball's Letters and parts of Piers Plowman, which she presents as two examples of allegorical literature associated with the Peasants' Revolution of 1381; Gower's allegorical representation of the Merciless Parliament of 1388 in Confessio Amantis; and Chaucer's brilliant literary handling of key events in the reign of Richard II. In addition Astell argues for a precise dating of Sir Gawain and the Green Knight between 1397 and 1399 and decodes the work as a political allegory.
""Contents""; ""Preface""; ""Abbreviations""; ""Introduction""; ""1 The Materia of Allegorical Invention""; ""2 â€œFull of Enigmasâ€?: John Ballâ€?s Letters and Piers Plowman""; ""3 Gowerâ€?s Arion and â€œCitheroâ€?""; ""4 Chaucerâ€?s Ricardian Allegories""; ""5 Penitential Politics in Sir Gawain and the Green Knight: Richard II, Richard of Arundel, and Robert de Vere""; ""6 Joan of Arc, Margaret of Anjou, and Maloryâ€?s Guenevere at the Stake""; ""Conclusion""; ""Notes""; ""Bibliography""; ""Index""
Includes bibliographical references (pages 167-212) and index.
Print version record.
English.
JSTOR
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Political poetry, English (Middle) -- History and criticism; Politics and literature -- Great Britain -- History -- To 1500.; Invention (Rhetoric); Rhetoric, Medieval; Allegory; Great Britain -- Politics and government -- 1154-1399.; Great Britain -- Politics and government -- 1399-1485.; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Poésie politique anglaise (moyen anglais) -- Histoire et critique; Invention (Rhétorique); Rhétorique médiévale.; Allégorie.; Grande-Bretagne -- Politique et gouvernement -- 1154-1399.; Grande-Bretagne -- Politique et gouvernement -- 1399-1485.; allegories (literary genre); LITERARY CRITICISM -- Medieval; Allegory; English literature -- Middle English; Invention (Rhetoric); Political poetry, English (Middle); Politics and government; Politics and literature; Rhetoric, Medieval; Great Britain; To 1500; Criticism, interpretation, etc; History